Hambatan Hukum dalam Diplomasi Maritim sebagai Alternatif Penyelesaian Sengketa Kelautan - Dita Birahayu (Perspektif Hukum, 2019)
Forms of Indonesia as an archipelagic state struggle began Juanda Declaration of 1957 to the United Nations on the Law of the Sea in 1982. As a form of struggle Negara Indonesia in defending its maritime territory, there are legal barriers in an effort to enforce the maritime vision requiring maritime diplomacy as one solution. Through maritime diplomacy, national interests can be accommodated. The complexity of the problems that arise in the maritime region of Indonesia, the government of Indonesia should strengthen sectors including sectors related to maritime law. The purpose of this study are expected to know at the same time prevent any obstacles that arise in the implementation of maritime diplomacy. This study uses normative.